The “Many Faces” and Complexities of Continuing Education units within today’s Higher Education Organizations: An Empirical Study - Sandria Stephenson (Adult Education Research Conference, 2009)
A qualitative methodology was used to identify higher education leaders’ understanding of continuing education units’ organization and program development. Using various metaphors, the study reveals that the way administrators conceptualize their units symbolically often determine their administrative strategies relative to organizational development and program planning issues within their parent organization.